POTENSI TEPUNG KENTANG HITAM (Coleus tuberosus) SEBAGAI PENSUBSTITUSI TERIGU PADA PEMBUATAN CAKE: Potential of Black Potato Flour (Coleus tuberosus) as Wheat Substition Of Cake - Siska Cicilia; Eko Basuki; Agustono Prarudiyanto; Ahmad Alamsyah; Dody Handito (Pro Food, 2018)
ABSTRACT Wheat flour is one type of flour that was often used for making various types of foods and dishes such as noodles, bread, biscuits, cakes, cookies, and porridge. Availability of wheat flour supplied from imports. The high demand for wheat flour because of the increasing needs of the food industry. Dependence on wheat flour can have a negative impact on the country's economy. One alternative wheat substitution is tubers such as black potatoes. The purpose of this study was to figure the best formulation in making cakes from wheat flour and black potato flour. The results showed that the more addition of black potato flour caused a decrease in moisture content, increase in ash content and protein levels and a decrease in the level of preference of panelists. Adding potato flour to 10% produces a cake that preferred by panelists. Keywords: cake, Coleus tuberosus, wheat substitution ABSTRAK Tepung terigu merupakan salah satu jenis tepung yang sering digunakan dalam membuat berbagai jenis makanan dan masakan seperti mie, roti, biskuit, cake, cookies, dan bubur. Ketersediaan tepung terigu disuplai dari impor. Tingginya permintaan tepung terigu karena kebutuhan industri makanan yang terus meningkat. Ketergantungan terhadap tepung terigu bisa berdampak buruk terhadap perekenomian negara. Salah satu alternatif pengganti terigu adalah tepung umbbi-umbian seperti kentang hitam. Tujuan penelitian ini adalah menentukan formulasi terbaik dalam pembuatan cake dari tepung terigu dan tepung kentang hitam. Hasil penelitian menunjukkan semakin banyak penambahan tepung kentang hitam menyebabkan penuruan kadar air, penngkatan kadar abu dan kadar protein serta penurunan tingkat kesukaan panelis. Penambahan tepung kentang hingga 10% menghasilkan cake yang disukai panelis. Kata Kunci : cake, kentang hitam, substitusi terigu